Operationalizing Behavior Change Theory as Part of Persuasive Technology: A Scoping Review on Social Comparison - Lemke, Mailin; de Vries, Roelof A. J. (Frontiers in Computer Science, 2021)
Theories from psychology or the social sciences are commonly used as a starting point when designing persuasive technologies that aim to evoke a specific behavior change. Ideally, using these theories would (1) help guide the design of the persuasive technology and (2) help evaluate and inform the theory. In this paper, we focused on the first aspect and looked at how papers report on how a theory guided the design of persuasive technology. We performed a scoping review focused on the operationalization of social comparison theory as part of persuasive design. We chose social comparison due to its ubiquitous use in persuasive design as well as its potential positive or negative influence on the user. The former requires careful consideration in a persuasive design prototype. We focused on the proceedings of the Persuasive Technology conference from 2006 to 2020 to gain an understanding of the use of social comparison theory as part of persuasive design. Twelve studies met our inclusion criteria. Explanations of how the theory guides design decisions leading to the final operationalization were sparse. We suggest that conducting manipulation checks and using a systematic approach to reporting design decisions including the potential grounding of design elements in theory could highlight and clarify theoretical insights, and could increase our understanding of how social comparison—and behavior change theory in general—could be efficiently operationalized in persuasive technologies.